GLOBAL SCIENCE GOVERNANCE: CASE OF INTERGOVERNMENTAL ORGANIZATIONS - M. V. Kharkevich; M. Yu. Tumanova; D. S. Korobov; S. N. Nedelko (Vestnik MGIMO-Universiteta)
The globalization of science leads to an increase in the transaction costs of scientific work due to the specifics of the institutional, linguistic, cultural, infrastructural and other conditions of this activity in individual countries, institutions, scientific fields, etc. In addition, the increase in transaction costs is also influenced by the increasing interdependence between scientists around the world. Science is, in principle, collective creativity, but today it is truly global, and global collective work is more difficult to organize and provide than local or regional. The article discusses the role of international government organizations in the governance of global science in the field of basic research. International governmental organizations are viewed primarily as bureaucratic structures, and basic science as club goods or a specific asset that is more effective to manage with the help of hierarchical bureaucratic structures. As a case study, the activities of the international government organization of the Joint Institute for Nuclear Research are investigated. The globalization of science leads to the need for its governance, as well as to the definition of criteria for the effectiveness of such governance. The article discusses two dimensions of effectiveness: endogenous (bureaucratic) and exogenous (real). Endogenous effectiveness suggests that the organization effectively implements its decisions. In case of international governmental organizations in the field of science, it means conducting planned scientific events, organizing conferences, workshops, field trips, signing cooperation agreements, and publish articles in authoritative journals. Exogenous effectiveness implies that the implementation of the measures taken leads to the solution of the general problem for which the organization was created – scientific discoveries, innovations, etc. In other words, the organization can extremely effectively ensure the implementation of extremely inefficient measures. Moreover, if the measures developed are effective, and the organization implements them inefficiently, the result will also be low. Therefore, it is important to consider both aspects when analyzing the effectiveness of an organization. The purpose of the article is to consider the contradictions associated with the diversity of governance forms using the example of international governmental organizations in the field of science. Science as a social practice develops in a network form of self-organization, while international governmental organizations are instruments of bureaucratic (hierarchical) governance. The main thesis of this article is that under the conditions of globalization, the governance of basic science is carried out more effectively with the help of international intergovernmental organizations. To prove this thesis, the article uses the case study method, namely, the case of an international intergovernmental organization in the field of nuclear physics, the Joint Institute for Nuclear Research (JINR) in the Russian city of Dubna.